2006
DOI: 10.21273/jashs.131.5.586
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Effect of Winter Gibberellic Acid Sprays and Auxin Applications on Crop Value of `Clausellina' Satsuma

Abstract: A winter gibberellic acid (GA3) spray consistently reduced flower formation, but had a variable effect on the amount of first-grade fruit in the early harvest of `Clausellina' satsuma (Citrus unshiu Marc.), and in the long term these applications had no significant effect on the value of the crop. Auxin applications increased the amount of first grade-early harvested fruit, and increased crop value as compared to hand-thinned trees. No significant differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 11 publications
1
6
0
2
Order By: Relevance
“…No effect of year 1 yield was detected on mixed-type shoots (inflorescences containing flowers and leaves at various ratios), only on generative buds (inflorescences carrying only flowers with no leaves). Indeed, while fruit load and flowering manipulations by various means, such as defruiting, GA treatment and fall girdling, are highly effective on generative inflorescences, their effect on mixed-type shoots is not always significant [3] , [5] , [15] , [16] , [51] [53] .…”
Section: Discussionmentioning
confidence: 99%
“…No effect of year 1 yield was detected on mixed-type shoots (inflorescences containing flowers and leaves at various ratios), only on generative buds (inflorescences carrying only flowers with no leaves). Indeed, while fruit load and flowering manipulations by various means, such as defruiting, GA treatment and fall girdling, are highly effective on generative inflorescences, their effect on mixed-type shoots is not always significant [3] , [5] , [15] , [16] , [51] [53] .…”
Section: Discussionmentioning
confidence: 99%
“…These characters could be modified with the use of plant growth regulators (PGRs) if their use is permitted under national regulations as, for example, in the USA, Italy, Australia, and Chile (Ferrara et al 2015). Previous studies presented that plant growth regulators play an important role in fruit production, such as increase in berry weight of grape (Casanova et al 2009), enlargement of fruit size in grape (Xu et al 2019), apple (Muchjajib et al 2016) and mandarin (Duarte et al 2006), improving fruit set in mango (El Gammal et al 2015), reducing fruit drop in apple (Khandaker et al 2015), enhancing yield and quality of pomegranate (Adi Reddy & Manohar Prasad 2012), and delaying ripening of grapes (Ponce et al 2002). Forchlorfenuron (CPPU), a synthetic cytokinin, and gibberellic acid (GA3) are commonly applied by table grapes producers to improve berry size and firmness (Du Plessis 2008;Zoffoli et al 2009;Xu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the vast majority of experiments run on floral induction have shown that exogenous GA applications during the induction period reduce the quantity of flowers [8590]. If we take into account that flowering is usually induced through stresses, such as low temperatures [91,92] or water stress [93], once again it would seem that GA has an antagonistic effect on stress hormones like ABA.…”
Section: Discussionmentioning
confidence: 99%
“…In most of the reviewed studies (Fig 8), exogenous GA applications during the induction period consistently reduced flower formation [85,87,89,90,97,98,106,102,107–111], while the application of Paclobutrazol (PBZ), a known antagonist of GA, increased the number of flowers [90,108]. As when temperature and water stress were manipulated for floral induction, GA also affected inflorescence type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation